The social life of forensic evidence and the epistemic sub-cultures in an inquisitorial justice system: Analysis of Saltão case. Issue 5 (September 2019) - Costa, Susana; Santos, Filipe
Highlights: Analysis of the proceedings of a homicide case in Portugal Examination of the construction of evidence according to epistemic culture Judicial sub-cultures are highlighted by their distinct understandings of forensics. Narratives biases the assessment of evidence with prejudice to justice.